2019
DOI: 10.1055/s-0039-1677761
|View full text |Cite
|
Sign up to set email alerts
|

Describing How School-Based SLPs Determine Eligibility for Children with Speech Sound Disorders

Abstract: The purpose of this study was to explore how school-based speech–language pathologists (SLPs) determine eligibility for children with speech sound disorders (SSDs). Presently, there is substantial variability nationwide with respect to if or how children with SSDs receive speech therapy in public schools. We report the results of a nation-wide survey of school-based SLPs, which further underscore this variability. Findings provide insight into which and how many factors SLPs report contributing to eligibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…A recent study revealed that only 37.3% of SLPs in Taiwan collected and analyzed connected speech samples in their clinical practice (Chang & Yeh, 2019). Similar results were found in a nationwide survey conducted in the United States; although over 90% of school-based SLPs reported collecting a speech sample as part of their eligibility data, that is, if a child may receive speech therapy services at school (Farquharson & Tambyraja, 2019), only 36% reported always collecting a connected speech sample, whereas 44% of them reported collecting connected speech samples only sometimes (Skahan et al, 2007). In sum, to elicit a more appropriate and representative connected speech sample in SSD assessment requires careful consideration.…”
supporting
confidence: 80%
“…A recent study revealed that only 37.3% of SLPs in Taiwan collected and analyzed connected speech samples in their clinical practice (Chang & Yeh, 2019). Similar results were found in a nationwide survey conducted in the United States; although over 90% of school-based SLPs reported collecting a speech sample as part of their eligibility data, that is, if a child may receive speech therapy services at school (Farquharson & Tambyraja, 2019), only 36% reported always collecting a connected speech sample, whereas 44% of them reported collecting connected speech samples only sometimes (Skahan et al, 2007). In sum, to elicit a more appropriate and representative connected speech sample in SSD assessment requires careful consideration.…”
supporting
confidence: 80%